Motivational Antecedents in Call Center Industry - Saeed, Hamid; Rajan, Thanachelvan a/I; Butar-Butar, Herry Fernades; Sameem, MAM (Politeknik Ilmu Pemasyarakatan, 2024)
To make the employees perform their task in the most efficient manner has always been tough for the management. To achieve this goal, management is required to have proper understanding of various factors that encourage motivation in employees. Since the last decade, there is rapid increase in a trend of call center industry in Pakistan. Nowadays, numerous foreigner businesses have outsourced their customer services and tele sales in developing countries like Pakistan. This study is intended to highlight all those factors that play an important role for encouraging motivation level of employees in Call Center Industry of Lahore. This research discusses the effect of Autonomy, Justice, Rewards and Recognition and Training on Employees motivation in the selected industry. To conduct the study, primary data is collected, and statistical tests are applied to measure the relationship between our supposed dependent and independent variables.